High dielectric and breakdown performances achieved in PVDF/graphene@MXene nanocomposites based on quantum confinement strategy. Issue 11 (1st August 2020) - Feng, Yefeng; Zhou, Furong; Dai, Yanmin; Xu, Zhichao; Deng, Qihuang; Peng, Cheng
Abstract: Graphene nanosheets are widely employed for fabricating high-dielectric-constant polymer nanocomposites for energy storage. However, severely reduced electric breakdown strengths of composites with increasing graphene content limit their high-field applications. To improve breakdown strengths of polyvinylidene fluoride/graphene composites without sacrificing dielectric constants, in this work, we proposed a rational strategy of constructing MXene quantum dot inter-layers for preparing ternary composites with desirable electric properties, owing to inter-layer induced quantum confinement and Coulomb blockade effects. Graphene oxide@nitrogen-doped Ti3 C2 MXene quantum-dot hybrid nanoparticles were synthesized via hydrogen-bond induced self-assembly route. Binary polymer/graphene and ternary polymer/hybrid-particle nanocomposite films were fabricated by solution cast process. Compared with binary composites, ternary counterparts have synergistically improved dielectric constants and breakdown strengths. Repeated disorder-bounce of electrons and strong coupling between electrons and holes, inside each quantum dot, might be responsible for superior electric performances of ternary composites. High dielectric constant ( 53@1 kHz) and breakdown strength ( 205 MV m −1 ) were realized in ternary composite with 0.12 wt % of nanoparticles. This work might pave a road for large-scale fabrication of high-performance nanocomposite dielectrics for energy storage.